2015
DOI: 10.1007/s11096-015-0137-9
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of clinical pharmacy services: an overview of systematic reviews (2000–2010)

Abstract: Systematic reviews that assessed clinical pharmacy services targeting specific conditions were more conclusive given that the intervention was well defined, and the measured outcomes were unequivocal and tangible. Conversely, the results were inconclusive for interventions with a broader target and with monitoring parameters that were unclearly established or inconsistently assessed across studies. These findings emphasize the need to better define clinical pharmacy services and standardize methods that assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
81
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(92 citation statements)
references
References 80 publications
4
81
0
3
Order By: Relevance
“…Pharmacist roles are dynamic and have evolved from providing patient support on medication use to being a clinical decision‐making team member across a range of specializations. Indeed, the role of pharmacists in providing a high level of patient care in DSM that improves patient outcomes and saves the health care system money has been well documented . In the present investigation we found that WV pharmacists generally have ambivalent attitudes toward DSM, regardless of their gender, CDE status, graduation institution type, or number of years in practice.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Pharmacist roles are dynamic and have evolved from providing patient support on medication use to being a clinical decision‐making team member across a range of specializations. Indeed, the role of pharmacists in providing a high level of patient care in DSM that improves patient outcomes and saves the health care system money has been well documented . In the present investigation we found that WV pharmacists generally have ambivalent attitudes toward DSM, regardless of their gender, CDE status, graduation institution type, or number of years in practice.…”
Section: Discussionsupporting
confidence: 89%
“…Indeed, the role of pharmacists in providing a high level of patient care in DSM that improves patient outcomes and saves the health care system money has been well documented. 18,20,25 In the present investigation we found that WV pharmacists generally have ambivalent attitudes toward DSM, regardless of their gender, CDE status, graduation institution type, or number of years in practice. Despite this, the majority of WV pharmacists and their employers have shown interest in understanding DSM by encouraging pharmacists to actively engage in continuing education programs that solidify their clinical knowledge.…”
Section: Discussionsupporting
confidence: 44%
“…In several countries professional pharmacy services are being remunerated and pharmacies are beginning to implement, however the implementation process pharmacies are undergoing is largely unknown [10]. Pharmacy practice research remains predominantly focused on clinical and cost effectiveness of the professional services [11], barriers and facilitators [1215], pharmacy culture [16], perception of pharmacy [10, 17], and remuneration [18, 19]. …”
Section: Introductionmentioning
confidence: 99%
“…Broad and unclear monitoring targets lead to inconclusive evidence in the evaluation of the impact of CP services. More conclusive evidence for the effectiveness of CP services are reported when the interventions are rigorously defined, in specific medical conditions, and when there are unequivocal outcomes 23. Often, pharmacists are sole practitioners when providing specialist services, which makes unpicking and measuring their individual clinical contributions relatively straightforward.…”
Section: Introductionmentioning
confidence: 99%